2015
DOI: 10.1007/s40436-015-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual phase titanium alloy hot forging process design: experiments and numerical modeling

Abstract: With an urgent demand of energy efficient coatings for building fenestrations, vanadium dioxide (VO 2 )-based thermochromic smart coatings have been widely investigated due to the reversible phase transition of VO 2 at a critical transition temperature of 68°C, which is accompanied by the modulation of solar irradiation, especially in the near-infrared region. As for commercial applications in our daily life, there are still some obstacles for VO 2 -based smart coatings, such as the high phase transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…However, if a defective microstructure occurs during the forging process, it is difficult to modify it by subsequent heat treatment. Furthermore, titanium alloys are extremely sensitive to the forging process, during which the temperature history determines the solid phase transformation and influences the shape, size, proportion, and distribution of phases [ 9 ]. Due to the difficulties in filling dies with the alloy to get the designed geometry, titanium alloys are classified as difficult-to-forge materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, if a defective microstructure occurs during the forging process, it is difficult to modify it by subsequent heat treatment. Furthermore, titanium alloys are extremely sensitive to the forging process, during which the temperature history determines the solid phase transformation and influences the shape, size, proportion, and distribution of phases [ 9 ]. Due to the difficulties in filling dies with the alloy to get the designed geometry, titanium alloys are classified as difficult-to-forge materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, if a defective microstructure occurs during the forging process, it is difficult to modify it by subsequent heat treatment. Furthermore, titanium alloys are extremely sensitive to the forging process, during which the temperature history determines the solid phase transformation, and influences the shape, size, proportion, and distribution of phases [9]. Due to the difficulties in filling dies with the alloy to get the designed geometry, titanium alloys are classified as a difficult-to-forge materials.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [14] reported the phase transition characteristics of a Ti-6Al-4V drum during hot forging and subsequent cooling operations. Furthermore, based on 3D FE approaches, Ducato et al [15] reflected the phase transition behaviors in a Ti-6Al-4V flange hot forging procedure. Buffa et al [16] studied Ti-6Al-4V phase distributions during a welding process and verified the simulated results by experiments.…”
Section: Introductionmentioning
confidence: 99%